CLIMATE NEUTRALITY: CONTEMPORARY CHALLENGES FOR EUROPEAN POLICY (Вісник: Міжнародні відносини, 2024)
Background. The article examines issues related to challenges to European climate neutrality, which have arisen before the European Union due to Russian armed aggression in Ukraine. The authors emphasize that the European Union has set an ambitious goal of becoming the world's first climate-neutral continent. The implementation of these plans requires a coordinated position not only of the member states, but also of the EU partners. Russia's military aggression against Ukraine may affect the achievement of European climate goals, as this conflict is accompanied by a significant impact on the environment. The authors set a goal to analyze how the Russian military invasion of Ukraine can affect the achievement of climate neutrality. To achieve the goal, the following research tasks were defined, in particular, to characterize the basic principles of the strategy and tools of the EU climate policy, to show the impact of Russian aggression on the ecology of the EU, to determine whether the topic of the environmental consequences of Russian aggression in Ukraine is relevant for the European public, and to assess how Russian armed aggression can influence the achievement of the goals of European climate neutrality.